Conceptual Maps and Their Influence on Teaching for Understanding - Rodríguez Garzón, Libia Andrea; Rueda Vargas, Manuel Antonio (Universidad Pedagógica y Tecnológica de Colombia, 2019)
This work presents an educational experience with students of the sixth grade of the Pablo VI Educational Institution in Sotaquirá(Boyacá, Colombia), and seventh grade of the Sergio Camargo Educational Institution in Miraflores (Boyacá, Colombia) in the area of Natural Sciences and Environmental Education, during the first semester of the year 2017. The results of the first and second period in the area are contrasted once the proposed strategy has been applied. The fundamental objective is the significant understanding of scientific knowledge through conceptual maps, applied in the design and development of structured didactic units for sixth grade in natural sciences, which support the Research - Action methodology implemented for the proposal. It is based on theworks of Joseph Novak (1992), on conceptual maps; Meaningful learning, by David Ausubel (1963); and the epistemological contributions of David Perkins (2010) regarding Education for Understanding, and Julián de Zubiría Samper (2006) regarding pedagogical models and the meaning of education. With the implementation of structured didactic units based on conceptual maps, a significant knowledge of the natural sciences is promoted in the institution under study, allowing students not only to learn, but also to do it comprehensively.